2021
DOI: 10.32332/joelt.v9i1.2194
|View full text |Cite
|
Sign up to set email alerts
|

Indonesian EFL Teachers’ Perceptions of Task-Based Language Teaching Approach

Abstract: Task-based language teaching is an approach applying tasks as a key point of pedagogical instruments. This study explores teachers’ perceptions of task-based language teaching in the secondary school context in Indonesia. Descriptive qualitative research design is used with data collected by using questionnaires. This study used purposive sampling to choose the sample. The findings showed that most of the junior and senior high school EFL teachers appeared to embrace positive attitudes towards practicing task-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…The study of Sarigoz and Fişne (2019) revealed by utilizing an integrated language testing program that included 10-unit assessment tasks, TBA significantly increased the level of language learning in the 4th grade. The result of this study agreed with the results of Prianty et al (2021), since considerable similarities existed between these two. In the second study, teachers' perceptions of TBLT, including TBA were explored and the results demonstrated teachers' positive attitudes toward the utilization of TBLT, even though most of them had little knowledge about TBLT and assessment.…”
Section: International Studiessupporting
confidence: 90%
See 1 more Smart Citation
“…The study of Sarigoz and Fişne (2019) revealed by utilizing an integrated language testing program that included 10-unit assessment tasks, TBA significantly increased the level of language learning in the 4th grade. The result of this study agreed with the results of Prianty et al (2021), since considerable similarities existed between these two. In the second study, teachers' perceptions of TBLT, including TBA were explored and the results demonstrated teachers' positive attitudes toward the utilization of TBLT, even though most of them had little knowledge about TBLT and assessment.…”
Section: International Studiessupporting
confidence: 90%
“…Using Tayeb et al (2018), Sarigoz and Fişne (2019), Liu and Ren (2021), and Prianty et al (2021), study results in which all of them explored the washback effect of TBA, the present paper aimed to provide further evidence on the washback effect of TBA of vocabulary on EFL learners. The study of Sarigoz and Fişne (2019) revealed by utilizing an integrated language testing program that included 10-unit assessment tasks, TBA significantly increased the level of language learning in the 4th grade.…”
Section: International Studiesmentioning
confidence: 99%
“…However, despite these persistent and frequent curriculum revisions, ELT practices in Indonesia did not automatically alter in a unidirectional way. It was found that in spite of their positive perceptions and attitudes towards communicative approaches (Prianty et al, 2021), Indonesian teachers are still employing traditional teacher-centered approaches focusing on linguistic structures in their actual instructional practices (Kustati et al, 2018). Even though Indonesia has a philosophy of Gotong Royong which means working collaboratively, English teaching processes was mainly administered through teacher-centered paradigm (Sutiah, 2011).…”
Section: English Language Teaching In Indonesiamentioning
confidence: 99%
“…TBLT is an approach to language learning which focuses on presenting tasks to improve the acquisition of DOI: http://dx.doi.org/10.30998/scope.v7i1. 13854 Dias Fatatin Birrina, Ive Emaliana 35 knowledge and language skills (Prianty, Ngadiso, and Wijayanto, 2021). This approach has a tendency to help students increase their skills while communicating with others.…”
Section: Introductionmentioning
confidence: 99%
“…the language serves as the means for achieving the outcome, not as an end in its own right). Based on previous research in EFL contexts (for example, Prianty, Ngadiso, and Wijayanto, 2021;Richards and Rodgers 2014;Butler, 2011), a task's criterial features in TBLT can be summed up as follows: tasks are goaloriented activities, in which the English language is utilized for communication in order to achieve an outcome; tasks exclude English language-free activities; tasks should be authentic and engaging, and tasks should primarily focus on meaning.…”
Section: Introductionmentioning
confidence: 99%